Prehospital Emergency Cricothyrotomy in Dogs Part 1: Experiences With Commercial Cricothyrotomy Kits - Hardjo, Sureiyan; Palmer, Lee; Haworth, Mark David (Frontiers in Veterinary Science, 2021)
The surgical cricothyrotomy (CTT) has been recommended for emergency front of neck airway access (eFONA) during a cannot intubate, cannot oxygenate scenario for military working dogs (MWD) and civilian law enforcement working dogs (operational K9s). In prehospital and austere environments, combat medics and emergency medical service providers are expected to perform emergency medical care to working dogs and may only have emergency airway kits designed for humans at their disposal. The objective of this article is to provide a detailed description of the application of such devices in cadaver dogs and highlight potential alterations to manufacturer guidelines required for successful tube placement. The kits evaluated included the Portex® PCK, Melker universal cricothyrotomy kit and H&H® emergency cricothyrotomy kit. A novel technique for awake cricothyrotomy in the dog is also described, which can also be considered for in-hospital use, together with the open surgical method described for the H&H® kit. To the authors’ knowledge, this is the first publication documenting and providing instruction on the application of commercial cricothyrotomy kits in dogs.